Pengelolaan Supervisi Akademik Di SMP Negeri 5 Salatiga - Suhirman, Suhirman, Prof. Dr. Sutama, M.Pd, Dr. Samino. M.M (2015)
Suhirman. Q 100 130035. Management of Academic Supervise in SMP Negeri 5 Salatiga. Thesis of Post-Graduate Degree, Universitas Muhammadiyah Surakarta 2015. The purposes of this research are: 1. To describe the academic supervise planning in SMP negeri 5 Salatiga. 2. To describe the academic supervise implementation of SMP negeri 5 Salatiga. 3. To describe the followingup acts of the academic supervise in SMP negeri 5 Salatiga. This research applies qualitative method, specifically using phenomenologic qualitative approach. The location of the research is SMP Negeri 5 Salatiga, Salatiga, Central Java. The data are presented into two groups; those are primary data and secondary data that in form of photograph, archieve, and interview about the management of academic supervise in SMP Negeri 5 Salatiga. The data sources are supervisor, headmaster, vice-headmaster, teachers, and education officers. The methods of the data collection are deep interview, observation, and documentation; that are activities observation, document collection, and taking the relevant photographs. The methods of data analysis are data reduction, data presentation, and cconslusion. The result of the research are: 1) The academic supervise planning in SMP Negeri 5 Salatiga is going to be hold at the early of semester by arranging programmed schedule, arranging supervise instruments, and supervising, and also the establishment of supervisor team. Headmaster, Supervisor, teacher and education officers actively participate in planning the academic supervise. Academic supervise is socialized during in-house training, workshop, and teacher devising on the first Monday of the early semester. 2) The implementation of academic supervise of a supervisor are technically coming in a class, observing directly toward class activity, noting all the things occurred in class. The obstacle of this supervise implementation is due to the tight schedule of teachers' activity and the headmaster therefore it is hard to find a fair schedule for supervising. The management of the academic supervise in SMP Negeri 5 Salatiga is an activity hold by supervisor toward the teachers by visiting classes based on the schedule agreed together to see whether teachers face difficulties in teaching or not. There are three steps in order to supervise academics they are early meeting steps, class observation, and feedback meeting. 3) The management of the following up acts of academic supervise in SMP Negeri 5 Salatiga of a supervisor is by delivering the results of the benefits of the learning, and also discussing several things that should be corrected proposionally based on accurate data. The headmaster follows up the process by helding a workshop and inhause training.